First steps towards online personal dosimetry using computational methods in interventional radiology: Operator's position tracking and simulation input generation. (June 2020) - Abdelrahman, Mahmoud; Lombardo, Pasquale; Vanhavere, Filip; Seret, Alain; Phillips, Christophe; Covens, Peter
Abstract: Interventional radiologists/cardiologists are repeatedly exposed to low radiation doses which makes them the group of the highest occupational exposure and put them at high risk of stochastic effects. Routine monitoring of staff is usually performed by means of passive dosimeters. However, current personal dosimeters are subject to large uncertainties, especially in non-homogeneous fields, like those found in interventional cardiology (IC). Within the PODIUM (P ersonal O nline D osI metry U sing computational M ethods) research project, a user-friendly tool was developed based on MCNP code to calculate doses to the staff in IC. The application uses both the data of motion tracking system to generate the position of the operator and the data from the Radiation Dose Structure Report (RDSR) from the imaging device to generate time-dependent parameters of the radiation source. The results of the first clinical validation of the system show a difference of about 50% between simulated H p ( 10 ) with MCNP and measured H p ( 10 ) with electronic personal dosimeter worn above the lead apron. Highlights: MC simulations can accurately calculate doses in interventional radiology fields. Motion tracking system based on depth-cameras was developed to be used in cath-labs. An application was developed to generate MCNP input files from radiation dose reports. Clinical validation tests showed differences between measurements and simulations.